2022
DOI: 10.3389/fpls.2022.989406
|View full text |Cite
|
Sign up to set email alerts
|

Brittle culm 3, encoding a cellulose synthase subunit 5, is required for cell wall biosynthesis in barley (Hordeum vulgare L.)

Abstract: The cell wall plays an important role in plant mechanical strength. Cellulose is the major component of plant cell walls and provides the most abundant renewable biomass resource for biofuels on earth. Mutational analysis showed that cellulose synthase (CESA) genes are critical in cell wall biosynthesis in cereal crops like rice. However, their role has not been fully elucidated in barley. In this study, we isolated a brittle culm mutant brittle culm 3 (bc3) derived from Yangnongpi 5 ethyl methanesulfonate (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…The circulation of CSCs between the plasma membrane and various intracellular compartments plays a crucial role in determining the level of cellulose synthesis ( Vellosillo et al, 2021 ). Studies have demonstrated that several factors, such as transcription factors like MYB family proteins, SND1, VND family proteins, and signaling molecules including NO, NAA, and BR, can promote cellulose synthesis ( Guo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The circulation of CSCs between the plasma membrane and various intracellular compartments plays a crucial role in determining the level of cellulose synthesis ( Vellosillo et al, 2021 ). Studies have demonstrated that several factors, such as transcription factors like MYB family proteins, SND1, VND family proteins, and signaling molecules including NO, NAA, and BR, can promote cellulose synthesis ( Guo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brittle mutants have been extensively studied in various plant species, including rice [1,2], Arabidopsis thaliana [3,4], and barley [5]. The culms of these mutants typically exhibit decreased mechanical strength and increased brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…In barley (H. vulgare L.), the influence of cellulose synthase and cellulose synthase-like enzymes on the roots, stems, and associated biological reaction processes, achieved through their regulatory role in cellulose content, has been elucidated [15][16][17]. However, although one COBL gene associated with cellulose synthesis was pinpointed through genomewide association studies (GWAS) conducted to investigate cellulose content in barley [18], the information on COBL family genes and their effect on cellulose in barley remains unclear.…”
Section: Introductionmentioning
confidence: 99%